Adv
Deepak Bora
  • 0

Solve the following equation by factorisation.

  • 0

Quadratic Equation in one variable 

Share

Related Questions

Adv

1 Answer

  1. After Taking common and cross multiplying.

    (a+b-abx)(bx-1+ax-1) = 0

    (a+b-abx){(b+a)x-2}= 0

    ∴x= a+b/ab, x= 2/a+b

    • 1
Leave an answer

Leave an answer

Browse

Choose from here the video type.

Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs".

Captcha Click on image to update the captcha.